The Impact of the Digital Scrabble Game on Students’ Vocabulary in SMPN 32 Bengkulu Tengah - Melia Nurjannah; Iis Sujarwati; Kasmaini (International Journal of Innovation and Education Research, 2026)
One of the critical areas for using English effectively is vocabulary control. However, the vocabulary learning of many Indonesian junior high school learners in semi-rural areas is still problematic because they are not sufficiently exposed to English, and traditional learning activities are retained. The purpose of this research is to analyze the effect of digital-based Scrabble games, in this research is Scrabble GO, on the students’ vocabulary mastery at SMPN 32 Bengkulu Tengah. The study adopted the quantitative pre-experimental method with one-group pretest–posttest. Participants were 16 eighth-grade students from one intact class. A 20-item multiple-choice vocabulary test was administered before and after three treatment sessions using Scrabble GO. The data were analyzed using a paired samples t-test. The result showed that the mean score increased from 53.44 on the pretest to 58.75 on the post-test, representing a mean gain of 5.31 points. The paired samples t-test revealed a statistically significant difference between the pretest and post-test scores (p = .001). The results indicate that playing digital Scrabble games can help students significantly improve their vocabulary, behavior, and enhance their motivation and engagement in learning. Although the sample sizes in terms of number of participants are not large, and the research design is arguably not rigorous enough, this study represents early evidence on the use of digital game-based learning as an alternative means for classroom instruction at junior high schools. Keywords: Digital Scrabble, Game-Based Learning, Vocabulary Mastery